The roles of HD-ZIP proteins in plant abiotic stress tolerance - Li, Yuxia; Yang, Zongran; Zhang, Yuanyuan; Guo, Jinjiao; Liu, Lili; Wang, Chengfeng; Wang, Baoshan; Han, Guoliang (Frontiers in Plant Science, 2022)
Homeodomain leucine zipper (HD-ZIP) proteins are plant-specific transcription factors that contain a homeodomain (HD) and a leucine zipper (LZ) domain. The highly conserved HD binds specifically to DNA and the LZ mediates homodimer or heterodimer formation. HD-ZIP transcription factors control plant growth, development, and responses to abiotic stress by regulating downstream target genes and hormone regulatory pathways. HD-ZIP proteins are divided into four subclasses (I–IV) according to their sequence conservation and function. The genome-wide identification and expression profile analysis of HD-ZIP proteins in model plants such as Arabidopsis (Arabidopsis thaliana) and rice (Oryza sativa) have improved our understanding of the functions of the different subclasses. In this review, we mainly summarize and discuss the roles of HD-ZIP proteins in plant response to abiotic stresses such as drought, salinity, low temperature, and harmful metals. HD-ZIP proteins mainly mediate plant stress tolerance by regulating the expression of downstream stress-related genes through abscisic acid (ABA) mediated signaling pathways, and also by regulating plant growth and development. This review provides a basis for understanding the roles of HD-ZIP proteins and potential targets for breeding abiotic stress tolerance in plants.